Manajemen Sumber Daya Manusia Global dalam Meningkatkan Kinerja Perusahaan - Rezi Ardiansyah; Arya Putra Pracandra; Diajeng Putri Ambar Sari; Sabrina Meisa Rahmawati; Muhammad Asrul Fajri; Dewi Nuraini (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
In the dynamic era of globalization, Human Resource Management (HRM) has become key to success for companies in the global market. Global HRM involves an approach that considers global factors such as culture, labor regulations, and market demands. Challenges include adapting to cultural diversity, varying labor regulations, and managing dispersed teams. However, global HRM also presents opportunities, including broader access to global talent. Through detailed analysis, this journal aims to provide valuable insights for HRM practitioners and company leaders in managing human resources in the globalization era. The research method used is qualitative and descriptive, with literature studies as the data source. The research results highlight the importance of global human resource management in achieving organizational goals in diverse global markets. Proposed solutions include flexibility, effective resource management, cultural awareness enhancement, and employee engagement. With the implementation of effective HRM policies, organizations can enhance their performance and achieve their business goals in the global business era